Differences in outcome and toxicity between Asian and caucasian patients with lung cancer treated with systemic therapy. (April 2012) - Soo, Ross A; Kawaguchi, Tomoya; Loh, Marie; Ou, Sai-Hong I; Shieh, Marie P; Cho, Byoung-Chul; Mok, Tony S; Soong, Richie
It is increasingly recognized that differences in overall survival and toxicity exist between Asian and caucasian patients with small-cell and non-small-cell lung cancer, with a longer survival, higher response rates and greater toxicity to chemotherapy and targeted therapy reported in Asian patients. Two global studies are used to illustrate how the proportions of Asian patients can influence survival outcome. Ethnicity is an important and complex characteristic that should considered in the design and conduct of a global clinical study, as the safety, tolerability and response may vary between Asian and caucasian patients. Whether ethnic differences in lung cancer survival are attributed to genetic differences among races or are simply a surrogate marker of differences in access to healthcare because of socioeconomic differences is unclear. Carefully designed prospective studies investigating ethnic-specific determinants of sensitivity and toxicity to systemic therapy are warranted.